STUDENT SELF-GOVERNANCE AS A WAY OF EMPOWERMENT IN THE SYSTEM OF HIGHER EDUCATION - Бескорса, Олена; Максимюк, Альона (Професіоналізм педагога: теоретичні й методичні аспекти, 2020)
The article outlooks the issue of empowering in education through organizing student self-governance. The relevance of the research is proved by “European Convention on Human Rights” that was adopted by Council of Europe in 1994 and supported by Ukrainian government. Some changes have been made in the sphere of education, student self-governance is considered to protect students’ rights and interests and involve them into the management of educational institution. The analysis of scientific works of the domestic and foreign is presented in the article. The conceptual framework of the paper comprises the works by P. Freire, P. Hodkinson, T. Lawson, and J. Walker. The Ukrainian scientists I. Anosov, V. Demchuk, H. Harbuzova, Yu. Krashchenko, V. Prykhodko, V. Solovei, L. Sheina, L. Shyhapova, L. Vozniak pay special attention to different aspects of implementing self-governance in educational institutions. The purpose of the paper is to describe the student self-governance as a way of empowerment of human rights in education. It is defined that the foundations of the empowerment in education are revealed in the work of P. Freire where he stresses that students need to be actively involved in that learning and governing in order to have emancipatory effects. The concept of empowerment in education was first defined in the late 20th century by foreign scientists in the sphere of sociology and psychology (I. Cunningham, J. Hyman, and C. Baldry) who assert that empowerment means keeping control over different aspects of educational process and being responsible for quality of knowledge and skills gained. The authors emphasize that some aspects of empowerment correlates with the functions of student self-governing at educational institutions. Based on V. M. Pevsner’s research on the pedagogical potential of student self-governance, three main criteria for empowerment are singled out. It is concluded that the empowerment in education through implementing self-governance can help people understand the different beliefs, attitudes and values, as well as the glaring contradictions of today’s multicultural society in which they live.